2015
DOI: 10.1002/cncr.29738
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 122 advanced‐stage cutaneous squamous cell carcinomas by comprehensive genomic profiling opens the door for new routes to targeted therapies

Abstract: BACKGROUND:The authors hypothesized that comprehensive genomic profiling of advanced-stage cutaneous squamous cell carcinoma (cSCC) could identify genomic-derived drug targets of therapy for patients with conventional therapy-resistant disease. METHODS: Comprehensive genomic profiling of 315 cancer genes was applied to 50 ng of DNA from 122 cSCC cases for the evaluation of all classes of genomic alterations (GAs). Clinically relevant genomic alterations (CRGAs) were defined as those identifying anticancer drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 45 publications
3
82
1
1
Order By: Relevance
“…1618 Unfortunately, many of these mutations occur in tumor suppressor genes, for which therapeutic interventions are challenging. Notably, EGFR activating mutations were infrequently seen in these reports and others, 1921 and are therefore unlikely to explain the ORR associated with gefitinib in our study. In our previous trial of neoadjuvant gefitinib in CSCC, we did not identify any associations between EGFR mutations, gene copy number gains, or protein expression/phosphorylation and outcomes.…”
Section: Discussioncontrasting
confidence: 55%
“…1618 Unfortunately, many of these mutations occur in tumor suppressor genes, for which therapeutic interventions are challenging. Notably, EGFR activating mutations were infrequently seen in these reports and others, 1921 and are therefore unlikely to explain the ORR associated with gefitinib in our study. In our previous trial of neoadjuvant gefitinib in CSCC, we did not identify any associations between EGFR mutations, gene copy number gains, or protein expression/phosphorylation and outcomes.…”
Section: Discussioncontrasting
confidence: 55%
“…Numerous studies using nextgeneration sequencers have revealed clinically relevant genetic alterations in various tumors, and some researchers have recently advocated the clinical use of next-generation sequencers. [15][16][17][18][19][20] This is the first study to establish a clinical sequencing system for meningioma, which is the most common brain tumor.…”
Section: Discussionmentioning
confidence: 99%
“…(138) Comparable results were seen in more recent genomic profiling by Al-Rohil et al (2016) of 122 cSCC cases looking at both primary (63%) and metastatic (37%) lesions. (139) Across these samples they identified a total of 1120 genomic alterations with 88% of cSCCs harbouring at least one clinically relevant genomic alteration (CRGA) for which there is an anticancer drug already on the market or in clinical trial. The most common CRGA was in NOTCH1 (43%)…”
Section: Genetic Profile Of Cscchn With and Without Pnsmentioning
confidence: 99%
“…(140) To date, there have been very few gene-profiling studies to identify driver genes involved in perineural invasion or spread. Using microarray expression analysis to analyse more than 20,000 genes, Mays et al (2015) identified 24 differentially expressed genes between specimens of cSCC with and without microscopic PNI, none of which before had been implicated in perineural disease.…”
Section: Genetic Profile Of Cscchn With and Without Pnsmentioning
confidence: 99%